Maggots: Antimicrobial Stewards and Life Savers - Caitlin Trottier; Shamsuddin Anwar; Lisa Baxter; Natalie Nierenberg (Annals of Internal Medicine: Clinical Cases)
Maggots have been used in wound care for centuries. Their larvae secrete digestive enzymes and antimicrobial compounds that reduce the bacterial load within a wound and promote the growth of new, healthy tissue. We will discuss a series of patients with complex, nonhealing and life-threatening sacral wounds who developed multidrug-resistant sacral osteomyelitis. These wounds had failed to respond to standard and advanced strategies. Medicinal maggots were offered as a last-ditch effort in each case. In addition to saving the patients’ lives, these maggots demonstrated their underappreciated and underused role as antimicrobial stewards.